Angielski handel zewnętrzny (i kolonialny) w latach 1715–1740. Amerykanizacja rynku pozauropejskiego - Robak, Piotr (Przegląd Nauk Historycznych, 2013)
The article is focused on the presentation of the main directions of a growth of English foreign (and colonial) trade in the peacetime period in the international relationals in the Atlantic sphere between 1715–1740. The English overseas statistics (especially based on the collected data by E.B. Schumpeter) have indicated that in the described period was the continuance of a growth of English foreign trade (so called in a historical literature „trade revolution”) which had the beginning in the second half of the XVIIth century. The trade was marked by a superiority of the traditional European markets (especially in the Northern Atlantic countries) with a positive balance but much more dynamic was the growth of English Extraeuropean trade (essentially the colonial trade) in so called the Atlantic sphere of English economy. The main role in the latter played the American market (from Canada to some Carraibean Isles) with some share of the Iberoamerican markets. The part of Atlantic English trade dominated the whole English Extraeuropean trade (so called by some historians the Americanisation of English trade). The latter, however, was an unprofitable with some exception of the Western African trade but thanks to the steady increase of the role of overseas imports (especially many colonial products) in the English Euro pean re-eksport the whole English foreign trade had a regular positive balance in the described period. The Americanisation of English Extraeuropaen trade made the main level of British-French colonial rivalry (with an important share of Spanish colonies in the both Americas) in the first half of the XVIIIth century. The rivalry brought to an end the peacetime period in the Atlantic sphere when the breaking out of British- Spanish colonial war united a farther growth of English foreign trade with the war of Empire (1739–1740).